2015
DOI: 10.1136/bmjstel-2015-000019
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic motivation of preclinical medical students participating in high-fidelity mannequin simulation

Abstract: IntroductionWhile medical schools strive to foster students’ lifelong learning, motivational theories have not played an explicit role in curricular design. Self-determination Theory is a prominent motivational theory. It posits that perceived autonomy, competence and relatedness foster intrinsic motivation. This study explores the effects of autonomy on intrinsic motivation in medical students participating in high-fidelity mannequin simulation.MethodsA non-randomised crossover trial compared first-year medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The 13 articles included (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) in this study were published from 2015 to 2022, all in English. Regarding their origin, with seven (54%) were from Europe, four (31.0%) from Asia, and two (15.0%) from North America.…”
Section: ❚ Resultsmentioning
confidence: 99%
“…The 13 articles included (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) in this study were published from 2015 to 2022, all in English. Regarding their origin, with seven (54%) were from Europe, four (31.0%) from Asia, and two (15.0%) from North America.…”
Section: ❚ Resultsmentioning
confidence: 99%
“…(2015) [ 26 ] USA Mixed 44 1 st ~ 4 th Chapman et al (2015) [ 27 ] UK Quantitative 273 All years Almeida et al (2015) [ 28 ] Ukraine Quantitative 140 N/A Chapman & Bottentuit-Rocha. (2016) [ 29 ] Dominican Rep. Qualitative 5 N/A Thoma et al (2015) [ 30 ] USA Quantitative 22 1 st Fares et al (2016) [ 2 ] Lebanon Quantitative 165 1 st & 2 nd Ayuob, Sayes & Deek. (2016) [ 31 ] Saudi Arabia Mixed 55 2 nd ~ 5 th Bridgeman et al (2016) [ 32 ] UK Quantitative 50 N/A Beigy et al (2016) [ 33 ] Iran Quantitative 355 3 rd & 4 th Raulkar & Saks.…”
Section: Resultsmentioning
confidence: 99%
“…A DEA is an EA that is closely related to the learners’ major or formal curriculum, while an IEA is relatively unassociated with them [ 10 ]. The former included 18 articles [ 25 , 30 , 33 , 39 , 44 , 46 , 48 , 49 , 51 , 57 60 , 66 , 69 , 71 , 73 , 76 ] and the latter comprised 47 articles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High motivation has been one of the vital components during selections or interviews for the course of medicine [34-36]. Previously, it has also been reported that there was no significant difference in the level of intrinsic motivation among medical students who participated in high-fidelity mannequin simulation, as the medical students were found to be originally highly intrinsically motivated [37]. This was well reflected by our medical students who portrayed intrinsic motivation, mainly self-motivation, and self-discipline in coping with this tough time.…”
Section: Discussionmentioning
confidence: 99%